Pertuzumab combined with trastuzumab compared to trastuzumab in the treatment of HER2-positive breast cancer: A systematic review and meta-analysis of randomized controlled trials - Liu, Xiaoyun; Fang, Yingying; Li, Yinjuan; Li, Yan; Qi, Lu; Wang, Xinghe (Frontiers in Oncology, 2022)
Objective: Although dual anti-HER2 therapy, namely pertuzumab plus trastuzumab, has shown promising results in patients with HER2-positive breast cancer (BC), it is still unclear whether the dual therapy will increase adverse effects (AEs) while ensuring the efficacy compared with trastuzumab monotherapy. We conducted a systematic review and meta-analysis to compare the efficacy and safety of the combined therapy with monotherapy. Methods: A systematic search was performed to identify eligible randomized controlled trials (RCTs) that evaluated the administration of dual anti-HER2 therapy (pertuzumab plus trastuzumab or trastuzumab emtansine (T-DM1)) versus monotherapy (trastuzumab or T-DM1). Primary endpoints were overall survival (OS) and progression-free survival (PFS). Results: 14 RCTs (8,378 patients) were identified. Compared to monotherapy, dual therapy significantly improved the OS (HR=0.77, 95%CI: 0.59-0.99) and PFS (HR=0.74, 95%CI: 0.63-0.86) in advanced BC. In neoadjuvant therapy, dual blockade has a higher ORR rate than monotherapy. Grade 3 or higher febrile neutropenia, diarrhea and anemia, heart failure were more frequently reported in dual therapy compared to monotherapy. No significant difference in serious AEs was observed between two groups. In subgroup analysis, compared to single-target therapy, the dual target therapy has a higher OS and PFS rate in Asian patients with advanced therapy, However, total grade>3 AEs and serious AEs were significantly higher in dual group in Asian patients. Conclusions: Our study confirms that the combination of pertuzumab and trastuzumab therapy couldsubstantially improve the outcome of patients with HER2-positive breast cancer and was well tolerated compared to trastuzumab monotherapy.